2016
DOI: 10.1210/jc.2015-3604
|View full text |Cite
|
Sign up to set email alerts
|

Association Between HbA1cVariability and Risk of Microvascular Complications in Adolescents With Type 1 Diabetes

Abstract: Greater HbA1c variability predicts retinopathy, early nephropathy, and CAN, in addition to established risk factors, in adolescents with T1D. Minimizing long term fluctuations in glycemia may provide additional protection against the development of microvascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 36 publications
5
87
2
Order By: Relevance
“…Studies by other authors did not reveal any difference in hsCRP levels in patients with duration of diabetes up to 1 year versus T1DM patients with history of diabetes longer than 1 year either [47, 48]. On the other hand, lack of difference in hsCRP levels and lack of correlation with serum IL12 levels may suggest “good metabolic memory” and persistence of stable inflammatory state [49, 50]. Chronic hyperglycaemia is accompanied by inflammatory state in patients with longer duration of type 1 diabetes [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Studies by other authors did not reveal any difference in hsCRP levels in patients with duration of diabetes up to 1 year versus T1DM patients with history of diabetes longer than 1 year either [47, 48]. On the other hand, lack of difference in hsCRP levels and lack of correlation with serum IL12 levels may suggest “good metabolic memory” and persistence of stable inflammatory state [49, 50]. Chronic hyperglycaemia is accompanied by inflammatory state in patients with longer duration of type 1 diabetes [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…As far as DR is concerned, in patients with type 1 diabetes mellitus, Picconi et al have shown that early structural damage of neuroretinal cells was related to glucose fluctuation and suggested that GV should be addressed even in the presence of good metabolic control [13], in line with Virk et al, who found that greater HbA1c variability was a predictor for DR [14]. On the other hand, the DCCT group suggested that within-day GV does not play an apparent role in the development of microvascular complications beyond the influence of the mean glucose [15].…”
Section: Commentarymentioning
confidence: 96%
“…This difference was attributed to GV. Numerous later studies have further indicated that GV plays an important role in the development and progression of DM complications . Hence, to prevent the occurrence of DR, optimized antidiabetic therapy should focus on not only HbA1c, but also GV.…”
Section: Discussionmentioning
confidence: 99%